AKHLAK SISWA DALAM MENGIKUTI KEGIATAN DIDIKAN SUBUH DI TPQ NURUL IKHSAN JORONG AMPANG GADANG KECAMATAN PANTI KABUPATEN PASAMAN - Elsa Sapitri; Arifmiboy; Irna Andriati; Iswantir M (KOLONI, 2022)
This research was motivated by a phenomenon that occurred in TPQ Nurul Ikhsan Jorong Ampang Gadang, Panti District, Pasaman Regency, when the dawn education activities took place some students had bad morals such as how to get along with students who were not appropriate to friends, often said dirty words, called friends. with bad calls, not polite to teachers, and often sulking to teachers, therefore the author is interested in examining the causes of some of the students' morals are not good in participating in the dawn education activities at TPQ Nurul Ikhsan Jorong Ampang Gadang Sub-district of the Pasaman Regency. This study aims to determine the cause of students having poor morals in participating in the dawn education activities at TPQ Nurul Ikhsan Jorong Ampng Gadang, Panti District, Pasaman Regency. The approach used in this study is a qualitative approach, which describes the events that occur in the field as they are. The key informant in this study was TPQ student Nurul Ikhsan while the supporting informant was TPQ teacher Nurul Ikhsan, this study used interview and documentation techniques. The collected data was then analyzed using qualitative analysis techniques. Based on the findings of data analysis, it can be concluded that some of the students' morals towards teachers and friends are still not good, even though parents and teachers have shown good morals to students and set good examples, students' morals are still not good, this is caused by the playing environment. or student colleagues.  Keywords: Student morality, Dawn Education